Lipid oxidation that is, and is not, inhibited by vitamin E: Consideration about physiological functions of vitamin E - Niki, Etsuo (Free radical biology & medicine, 2021)
Lipids are oxidized in vivo by multiple oxidizing species with different properties, some by regulated manner to produce physiological mediators, while others by random mechanisms to give detrimental products. Vitamin E plays an important role as a physiologically essential antioxidant to inhibit unregulated lipid peroxidation by scavenging lipid peroxyl radicals to break chain propagation independent of the type of free radicals which induce chain initiation. Kinetic data suggest that vitamin E does not act as an efficient scavenger of nitrogen dioxide radical, carbonate anion radical, and hypochlorite. The analysis of regio- and stereo-isomer distribution of the lipid oxidation products shows that, apart from lipid oxidation by CYP enzymes, the free radical-mediated lipid peroxidation is the major pathway of lipid oxidation taking place in humans. Compared with healthy subjects, the levels of racemic and trans,trans-hydro (pero)xyoctadecadienoates, specific biomarker of free radical lipid oxidation, are elevated in the plasma of patients including atherosclerosis and non-alcoholic fatty liver diseases. α-Tocopherol acts as a major antioxidant, while γ-tocopherol scavenges nitrogen dioxide radical, which induces lipid peroxidation, nitration of aromatic compounds and unsaturated fatty acids, and isomerization of cis-fatty acids to trans-fatty acids. It is essential to appreciate that the antioxidant effects of vitamin E depend on the nature of both oxidants and substrates being oxidized. Vitamin E, together with other antioxidants such as vitamin C, contributes to the inhibition of detrimental oxidation of biological molecules and thereby to the maintenance of human health and prevention of diseases. [Display omitted] •Lipids are oxidized in vivo by multiple oxidizing species.•Antioxidant effect of vitamin E depends on oxidizing species and target substrate.•Vitamin E inhibits free radical mediated lipid peroxidation efficiently.•Vitamin E alone cannot cope with detrimental oxidative modification of lipids.•Multiple antioxidants are required to protect biological molecules from oxidation.